2012
DOI: 10.3109/07420528.2012.741173
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Wake Cycle of Adolescents in Côte d'Ivoire: Influence of Age, Gender, Religion and Occupation

Abstract: The human sleep-wake cycle is characterized by significant individual differences. Those differences in the sleep-wake cycle are partially heritable but are also influenced by environmental factors like the light/dark cycle or social habits. In this study we analyse for the first time the sleep-wake rhythm of adolescent pupils and working adolescents in a less industrialised country in West Africa near the equator. The aim of this study was to explore the sleep wake cycle in this geographical region, using Côt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
1
8
1
Order By: Relevance
“…Studies on effects of gender and age on sleep problems in children were scanty and the results were not consistent. There were evidences that sleep problems showed age or/and gender differences [44], but a recent study in Italian children suggested that no age and gender differences were observed in sleep problems [45]. Our study demonstrated that sleep problems of parasomnia and sleep-disordered breathing were higher prevalent in boys than in girls, wh ile sleep an xiety was higher p revalent in girls than in boys.…”
Section: Sleep Problemscontrasting
confidence: 44%
“…Studies on effects of gender and age on sleep problems in children were scanty and the results were not consistent. There were evidences that sleep problems showed age or/and gender differences [44], but a recent study in Italian children suggested that no age and gender differences were observed in sleep problems [45]. Our study demonstrated that sleep problems of parasomnia and sleep-disordered breathing were higher prevalent in boys than in girls, wh ile sleep an xiety was higher p revalent in girls than in boys.…”
Section: Sleep Problemscontrasting
confidence: 44%
“…Circadian typology (chronotype) is another influence on sleep habits, because individuals show variability in their sleep–wake timing preferences 11. These differences are partly innate, but are also shaped by environmental factors, such as daily light exposure (both natural and artificial), and may also be influenced by the seasonal photoperiod and the longitude and latitude of residence 12,13. Late chronotypes are at highest risk of sleep curtailment and disturbance, due to misalignment between their social and biological time 14.…”
Section: Introductionmentioning
confidence: 99%
“…This situation is not very different when it comes to children, whose typical school times and extracurricular activities reduce opportunities for daytime naps that are common among preschoolers. Furthermore, inadequate sleep in children has been related to attention deficits, irritability, emotional fragility and frustration (Dahl, 1996; Belísio et al, 2010). Changes in the sleep-wake cycle are thought to jeopardize school learning in two ways: they reduce the capacity for new learning, and impair the consolidation of what has already been learned (Louzada et al, 2008).…”
Section: Introductionmentioning
confidence: 99%